IMPLEMENTATION OF NO-SMOKING AREA POLICY IN THE REGIONAL DEPARTMENT OF EDUCATION AND CULTURE NORTH MOROWALI - Sudrajab Petalolo, Eli; Nuraisyah, Nuraisyah; Haryono, Dandan (Penerbit Lafadz Jaya, 2024)
This research is to determine the implementation of the Smoke Free Area Policy in the North Morowali Regency Regional Education and Culture Office. The type of research used is descriptive qualitative. Data types use primary data and secondary data. Data collection techniques are carried out through observation, interviews and documentation. The informant withdrawal technique uses purpose. The data analysis used is the Miles, Huberman and Saldana model, namely data collection, data presentation, data condensation and drawing conclusions. Based on the research results, it was found that the implementation of the smoke-free area policy in the North Morowali Regency Regional Education and Culture Office was relatively ineffective, namely the lack of intense communication and the lack of comprehensive and continuous outreach, only a few employees and visitors/community knew about it. regarding the existence of a smoke-free area policy. Meanwhile, regarding the resource aspect, the Regional Education and Culture Office of North Morowali Regency does not have the readiness to implement this policy due to the lack of resources. For example, there is no formation of an anti-smoking task force, there are no special smoking rooms for employees and visitors/public who want to smoke. Furthermore, the disposition factor is the leadership's lack of firmness in imposing fines and sanctions on policy violators. The final factor is the bureaucratic structure where there are no guidelines for implementing Standard Operating Procedures (SOP) in implementing these policies and cooperative relations between institutions are still very lacking.